Analisis Manajemen Pelayanan Hotel Syariah Perspektif Standar Pariwisata Halal : (Studi pada Hotel Syariah Bangkalan) - Galuh Mustika Argarini (Journal of Economic and Islamic Research, 2024)
Islamic hotels have become a trend, with many appearing in various cities emphasizing "syariah." However, a syariah hotel is not merely about the label; there needs to be clarity on its specifications and criteria to avoid it becoming solely a business commodity. Unlike Islamic financial institutions that have established operational standards, syariah hotels do not have universally defined operational standards set by Islamic bodies such as MUI (Indonesian Ulema Council) or the Department of Religious Affairs. This is a point of ongoing debate in society.   This research focuses on the application of halal tourism services in hotels visited by tourists, whether they adhere to syariah principles or not. The objectives of this study are: a) to analyze the management concept of syariah hotel services from the perspective of halal tourism standards at a syariah hotel in Bangkalan, and b) to analyze the supporting and inhibiting factors in the implementation of management standards for syariah hotel services from the perspective of halal tourism standards at a syariah hotel in Bangkalan.   This study employs a qualitative descriptive method with a case study approach. Data collection techniques include observation, interviews, and documentation. Data analysis follows Miles and Huberman's model with the following steps: data reduction, data display, and verification.   The research findings are as follows: a) The implementation of standardized halal tourism service management at the syariah hotel in Bangkalan complies with syariah principles in its services, as classified under the regulations, particularly Tourism and Creative Economy Regulation No. 12 of 2016 concerning Guidelines for the Operation of Syariah Hotels. The hotel has adjusted its operations since its establishment in anticipation of MUI certification. b) Supporting factors for the implementation of syariah hotel services in Bangkalan include its strategic location and adherence to syariah principles, reinforced by regulations or policies set by the Ministry of Tourism and Creative Economy No. 12 of 2016 regarding Guidelines for the Operation of Syariah Hotels. However, the inhibiting factor is that the syariah hotel in Bangkalan has not yet obtained MUI's syariah hotel business certificate due to ongoing procedures related to the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia No. 12 of 2016 concerning Guidelines for the Operation of Syariah Hotels.